Yabancı uyruklu (göçmen, sığınmacı vb.) çalışanların ülkemizde sigortalı ve sigortasız çalışma esnasında 6331, 4857 ve 5510 kanunlarına göre değerlendirmesi ve çalışanlara çalışma koşulları için anket hazırlanması - Aymelek, İsmail (My University, 2024)
Araştırma kapsamında; Yabancı uyruklu (göçmen, sığınmacı vb.) çalışanların ülkemizde sigortalı ve sigortasız çalışma esnasında 6331; 4857 ve 5510 kanunlarına göre değerlendirmesi ve çalışanlara çalışma koşulları için anket hazırlanması, çalışma mevzuatı açısından incelenmesi amaçlanmıştır. Araştırma kapsamında; araştırmanın örnekleminde yer alan yabancı çalışanların sigortalı ve sigortasız çalışma durumlarına yönelik çalışma mevzuatından kaynaklanan haklarına yönelik bilgi düzeyleri belirlenmiştir. Araştırma kapsamında ayrıca, yabancı çalışanların çalışma koşullarına yönelik görüşleri değerlendirilmiştir. Araştırmadan elde edilen bulgular doğrultusunda, yabancı çalışanların sigortalı ve sigortasız çalışma durumlarına yönelik çalışma mevzuatından kaynaklanan haklarına yönelik bilgi düzeylerinin yüksek olduğu saptanmıştır. Bununla birlikte yabancı çalışanların çalışma koşullarına yönelik görüşlerinin, genel olarak olumsuz olduğu bulgulamıştır.

In the scope of the research; 6331 of foreign nationals (immigrants, refugees, etc.) employees while working with or without insurance in our country; It is aimed to evaluate it according to laws 4857 and 5510, prepare a survey for employees about working conditions, and examine it in terms of labor legislation. In the scope of the research; The knowledge levels of foreign employees in the sample of the study regarding their rights arising from labor legislation regarding insured and uninsured employment were determined. Within the scope of the research, the opinions of foreign employees regarding working conditions were also evaluated. In line with the findings obtained from the research, it was determined that the level of knowledge of foreign employees regarding their rights arising from labour legislation regarding insured and uninsured working conditions was high. However, it was found that the opinions of foreign employees regarding working conditions were generally negative.
Foreign national (immigrants, asylum seekers etc.) employees while working in our country with or without insurance 6331; evaluation according to laws 4857 and 5510 and preparation of a survey for employees about working conditions
Keywords: Emigration and immigration; Foreign workers; Göç Turkish Law; Göç ve Göçmenlik; Hukuki durum, yasalar, vb; Immigration; Legal status, laws, etc; Turkey; Türk Hukuku; Türkiye; Yabancı işçiler; Yabancı İşçiler